The epileptic singers of belle époque Paris. Issue 2 (21st May 2012) - Baxendale, Sallie; Marshall, Fiona
Abstract : In late 19th century Paris, people with epilepsy were treated alongside those with hysteria in the now famous Salpêtrière Hospital, where both conditions were deemed to have a neurological basis. When Jean Martin Charcot became chief physician at the Salpêtrière Hospital in 1862, he described himself 'in possession of a kind of museum of living pathology whose holdings were virtually inexhaustible'. He opened the doors of his 'living museum' and exhibited his prize specimens to all of Paris. By putting his patients on display, Charcot introduced a vogue for pathology that permeated well beyond the world of medical enquiry and into the public psyche and vernacular. Not only did Charcot's demonstrations provide the inspiration for high culture in the form of operas, plays and novels, they also provided the inspiration for the 'gommeuses epileptiques' (epileptic singers), who entertained the masses at the café concerts. This paper explores the foundations of our current medical approaches to mental illness and epilepsy, with a particular focus on the boundaries that emerged between hysteria and epilepsy in 19th century Paris. These clinical boundaries were both shaped by and reflected in the popular entertainments in the city.